Bone Mineral Disease After Kidney Transplantation - Torregrosa, JV (2022)
Chronic kidney disease-mineral bone disorder (CKD-MBD) after kidney transplantation is a mix of pre-existing disorders and new alterations. The final consequences are reflected fundamentally as abnormal mineral metabolism (hypercalcemia, hypophosphatemia) and bone alterations [high or low bone turnover disease (as fibrous osteitis or adynamic bone disease), an eventual compromise of bone mineralization, decrease bone mineral density and bone fractures]. The major cause of post-transplantation hypercalcemia is the persistence of severe secondary hyperparathyroidism, and treatment options include calcimimetics or parathyroidectomy. On turn, hypophosphatemia is caused by both the persistence of high blood levels of PTH and/or high blood levels of FGF23, with its correction being very difficult to achieve. The most frequent bone morphology alteration is low bone turnover disease, while high-turnover osteopathy decreases in frequency after transplantation. Although the pathogenic mechanisms of these abnormalities have not been fully clarified, the available evidence suggests that there are a number of factors that play a very important role, such as immunosuppressive treatment, persistently high levels of PTH, vitamin D deficiency and hypophosphatemia. Fracture risk is four-fold higher in transplanted patients compared to general population. The most relevant risk factors for fracture in the kidney transplant population are diabetes mellitus, female sex, advanced age (especially > 65 years), dialysis vintage, high PTH levels and low phosphate levels, osteoporosis, pre-transplant stress fracture and high doses or prolonged steroids therapy. Treatment alternatives for CKD-MBD after transplantation include minimization of corticosteroids, use of calcium and vitamin D supplements, antiresorptives (bisphosphonates or Denosumab) and osteoformers (synthetic parathyroid hormone). As both mineral metabolism and bone disorders lead to increased morbidity and mortality, the presence of these changes after transplantation has to be prevented (if possible), minimized, diagnosed, and treated as soon as possible.